The Fourth Year of Medical School: Time for Reassessment. (5th July 2017) - Alman, Benjamin A.; Purtill, James J.; Pellegrini, Vincent D.; Scoles, Peter
Abstract : Abstract: Most U.S. medical schools follow the 4-year model, consisting of 2 preclinical years, core clinical experience, and a fourth year intended to permit students to increase clinical competency, to explore specialty areas, and to transition to residency. Although the design and delivery of Years 1 through 3 have evolved to meet new challenges and expectations, the structure of Year 4 remains largely unchanged. For most students considering a career in orthopaedics, Year 4 is a series of elective rotations in which educational objectives become secondary to interviewing for residency programs. Most accreditation bodies recognize the importance of attainment of competency over the duration of medical school as the goal of educating physicians, and thus, there is a growing interest in reexamining the traditional medical school curriculum with the goal of integrating the final phases of undergraduate education and the first phases of postgraduate education. A literature search was undertaken to identify publications on the duration of medical education. Pilot approaches to competency-based integration of undergraduate medical school and postgraduate training in orthopaedic surgery were reviewed. There have been few data suggesting that 4 years of medical education is superior to shorter-duration programs. Three approaches to competency-based integration of undergraduate medical school and postgraduate training are presented. Their goal is to use student and faculty time more effectively. Each approach offers the opportunity to lower the cost and to decrease the time required for Board Certification in Orthopaedic Surgery. Two approaches shorten the entire duration of medical school and graduate training by using various proportions of the fourth year to begin residency, and one approach expands the duration of orthopaedic training by starting in the fourth year of medical school and including training equivalent to a fellowship program into the residency experience. The effectiveness of such programs will form the basis for revisions to the current orthopaedic training paradigm, resulting in a more effective, efficient, and integrated orthopaedic training curriculum.